Olympus has fallen [videorecording (Blu-Ray)] - Fuqua, Antoine; Butler, Gerard, 1969-; Freeman, Morgan; Bassett, Angela; Eckhart, Aaron (Sony Pictures Home Entertainment, 2013)
When the president is kidnapped by a terrorist who seizes control of the White House (Secret Service Code: Olympus), disgraced former presidential guard Mike Banning finds himself trapped within the building. As the national security team rushes to respond, they must rely on Banning's insider knowledge to save the president and prevent an even greater catastrophe.